WirelessHART Networked Set-Point Weighted Controllers - Hassan, S.M. (Springer, 2020)
This chapter presents the development of SW and adaptive SW controller for WHNCS. The SW technique is a powerful and simple method based on the feed-forward strategy. The advantage of this method is that it can be employed to improve systems performance with respect to setpoint tracking ability and disturbance rejection capability. The design gives a two-degree-of-freedom controller in which the first degree of freedom gives good setpoint response while the second degree of freedom gives good disturbance rejection as well as good robustness to model mismatch and other uncertainties. This type of controller adequately falls within the class of controllers to solve the problem of stochastic delay, random noise, and uncertainties. Â© 2020, Springer Nature Switzerland AG.